Pertambangan Batu Kapur Ditinjau Dari Pasal 69 UU No. 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup dan Mashlahah (Studi di Sekapik Gresik) Nailatul Khofifi - Nailatul Khofifi (Journal of Islamic Business Law, 2018)
The purpose of this study is to determine the limestone mining practices in the village of Sekapuk Ujungpangkah sub-district Gresik regency viewed from article 69 of Law Number 32 Year 2009 on the Protection and Management of Environment and Mashlahah. This research includes empirical legal research using a qualitative approach. Then the data used in this study is the primary data obtained directly the results of interviews authors from the government apparatus, the miners and the community around the tabang area. While in obtaining data writer use method of interview and documentation. Then in the analysis using descriptive method with qualitative approach. The results of this study indicate that, firstly, mining in Sekapuk area was established by PT. Polowijo yag has been going on since 1980. Mining practices have been using modern tools so as to minimize the occurrence of environmental problems and the safety of the workers, as well as increased production. Second, mining activities owned by PT. Polowijo includes mining activities that are in accordance with environmental documents and not to damage the environment. Third, mining is very beneficial for the community around the mine by opening up employment opportunities for the surrounding community. So it can reduce the unemployment rate.